Correlation between clinical findings and self-care with the feet of patients with type 2 diabetes in the city of Mossoró-RN: A quali-quantitative approach - Cabral Duarte, Felipe; de Lima Firmino, Carlos Menandro; de Farias Alexandre, Allysson Felipe; Saldanha Diógenes, Emilli Joice (Journal of Health Care, 2025)
Introduction: Diabetes mellitus (DM) has a high worldwide prevalence, currently affecting around 537 million adults. The chronic hyperglycemic state promotes the development of complications, among them, the diabetic foot, which is one of the main responsible for causing the increase in the rates of non-traumatic lower limb amputations and the increase in hospital costs. In this context of the need to prevent diseases, the Sistema Salvando o Pé Diabético (SISPED) operates, a computational tool that offers greater efficiency in screening and monitoring in order to avoid serious outcomes. In addition to SISPED, self-care with the feet of patients with DM is also essential as a preventive measure in primary care. Objective: To correlate clinical findings and self-care with feet in patients with DM2 in primary care in the city of Mossoró-RN. Methods: This is an exploratory and descriptive study carried out in 5 Basic Health Units in Mossoró-RN, using the SISPED and a self-authored questionnaire about self-care of the feet directed to patients with DM2 for data collection. Results: In the clinical findings of the SISPED, a higher prevalence of the use of inappropriate footwear, dry/scaly feet and fissures/cracks was observed. In the assessment of self-care of the feet, the inefficiency of providing basic guidelines was verified. Conclusions:The high prevalence of clinical findings associated with diabetic foot is intrinsically related to inefficiency in performing self-care with the feet, requiring an immediate preventive intervention in primary health care.